Computational analysis of shock-induced flow through stationary particle clouds. (May 2019) - Osnes, Andreas Nygård; Vartdal, Magnus; Omang, Marianne Gjestvold; Reif, Bjørn Anders Pettersson
Highlights: Shock-induced flow through particle clouds is investigated using LES. First of a kind study of particle size influence on shock particle cloud interaction. Mean flow and fluctuation statistics are examined inside the particle cloud. A pseudo-turbulent Reynolds stress model is proposed. Abstract: We investigate the shock-induced flow through random particle arrays using particle-resolved Large Eddy Simulations for different incident shock wave Mach numbers, particle volume fractions and particle sizes. We analyze trends in mean flow quantities and the unresolved terms in the volume averaged momentum equation, as we vary the three parameters. We find that the shock wave attenuation and certain mean flow trends can be predicted by the opacity of the particle cloud, which is a function of particle size and particle volume fraction. We show that the Reynolds stress field plays an important role in the momentum balance at the particle cloud edges, and therefore strongly affects the reflected shock wave strength. The Reynolds stress was found to be insensitive to particle size, but strongly dependent on particle volume fraction. It is in better agreement with results from simulations of flow through particle clouds at fixed mean slip Reynolds numbers in the incompressible regime, than with results from other shock wave particle cloud studies, which have utilized either inviscid or two-dimensional approaches. We propose an algebraic model for the streamwise Reynolds stress based on the observation that the separated flow regions are the primary contributions to the Reynolds stress.